2019
DOI: 10.1063/1.5124402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZrO2 interfacial layer on forming ferroelectric HfxZryOz on Si substrate

Abstract: Ferroelectric HfxZryOz (HZO) with an average polarization switching window of 32 µC/cm2 was demonstrated on a Si substrate with a ZrO2 interfacial layer (IL). It is suggested that the ZrO2 IL below HZO crystallizes in the form of an o-phase prior to HZO crystallization, during rapid thermal annealing, thereby promoting the vertical growth of an o-phase HZO layer. HZO with the ZrO2 IL consists mainly of an o-phase that exhibits an in-plane tensile stress of 2.68 GPa, resulting in superior ferroelectric characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In contrast, FTJs are less sensitive to trapped charges during the readout process than FeFETs; however, similar reliability issues exist in FTJs based on ferroelectric/dielectric bilayers 191 . Several interfacial engineering methods, such as using a high‐k interlayer such as SiON, AlON, SiN x , ZrO 2 , Al 2 O 3 , or TiO 2 as the interlayer to replace SiO x , utilizing a scavenging layer, and optimizing annealing conditions, have been proposed to overcome these challenges, 27,124,125,169,192–203 and have showed impressive stability 96,99,192,204 . In addition to the properties related to device reliability, other key device performance parameters are scalability, switching speed, and programming energy.…”
Section: Neuromorphic Computing Systems Based On Fluorite‐structured ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, FTJs are less sensitive to trapped charges during the readout process than FeFETs; however, similar reliability issues exist in FTJs based on ferroelectric/dielectric bilayers 191 . Several interfacial engineering methods, such as using a high‐k interlayer such as SiON, AlON, SiN x , ZrO 2 , Al 2 O 3 , or TiO 2 as the interlayer to replace SiO x , utilizing a scavenging layer, and optimizing annealing conditions, have been proposed to overcome these challenges, 27,124,125,169,192–203 and have showed impressive stability 96,99,192,204 . In addition to the properties related to device reliability, other key device performance parameters are scalability, switching speed, and programming energy.…”
Section: Neuromorphic Computing Systems Based On Fluorite‐structured ...mentioning
confidence: 99%
“…Substituting the insulator with high‐k dielectrics could be an effective method to resolve these problems, contributing to the high reliability of FeFETs; SiON or SiN x can be used instead of pure SiO 2 27,192 . Several researchers comprehensively investigated the effect of ZrO 2 IL on the ferroelectric properties of Hf 1− x Zr x O 2 thin film on the Si substrate 199,200,213 . Their experimental results showed that the orthorhombic phase of ZrO 2 could promote the vertical growth of a non‐centrosymmetric orthorhombic phase in the Hf 1− x Zr x O 2 film, inducing in‐plane tensile stress on the Hf 1− x Zr x O 2 film.…”
Section: Neuromorphic Computing Systems Based On Fluorite‐structured ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the MFIS gate stack structures have been expected to be more suitable candidates for ferroelectric-based applications from the viewpoint of device scaling and robust ferroelectric characteristics compared to the MFMIS structures . However, the film thickness and material type of the IL should be carefully determined with important technical considerations of voltage distribution and capacitance coupling mismatch during the memory device operations because the ILs are inevitably required to secure sound interface characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the MFIS gate stack structures have been expected to be more suitable candidates for ferroelectric-based applications from the viewpoint of device scaling and robust ferroelectric characteristics compared to the MFMIS structures. 40 However, the film thickness and material type of the IL should be carefully determined with important technical considerations of voltage distribution and capacitance coupling mismatch during the memory device operations because the ILs are inevitably required to secure sound interface characteristics. In other words, for the devices with MFIS gate stacks, it is important to enhance the degree of the available saturated ferroelectric polarization and to reduce the depolarization field and leakage current components, which can be achieved by the decrease in physical thickness and increase in dielectric constant of the IL.…”
Section: Introductionmentioning
confidence: 99%